Green spaces and health in the city urban green spaces network planning for a healthful urban environment - Caligan, Krista Faye Marian A.
Green spaces are important for the ecosystem services that they provide and for their positive impact on human health and wellbeing. Unfortunately, rapid urbanization, urban densification, dissension of local government units, land developers, and landowners regarding the value of green spaces, and frustration regarding the lack of enabling mechanisms, such as plans and policies, to provide this service contribute to the ongoing loss of natural landcover and green spaces and mismatch between the supply of and demand for green spaces. This lack of green spaces coupled with the inequality of access to green spaces may be detrimental to human health. This study proposes an urban green spaces network plan that addresses the need of urban residents for a balanced and healthful environment by ensuring enough provision of green spaces and reducing inequality on access to green space. This was done by taking into account the green spaces, green corridors, and social values of the study site which is Quezon City and by exploring the relationship between green spaces and human health using different parameters related to green spaces such as barangay greenness, access to green spaces, population pressure on green spaces, and landscape fragmentation and the population health indicator which was the prevalence of obesity and overweight in children below five years old. With the help of GIS tools, barangays lacking green spaces were identified and suitable sites for green spaces development were determined. Existing and proposed green spaces are linked together through green corridors which run along the street network.